The Effect of Acupressure Points H7 and LI4 on Pain Intensity Post Caesarean Section in Women Giving Birth at Bhayangkara Hospital TK.I PUSDOKKES POLRI in 2024 - Suprihatin; Rahayu Kurniawati; Vivi Silawati (International Health Sciences Journal, 2024)
Postoperative pain is a common problem faced by mothers after undergoing a cesareansection. Effective pain management is essential to accelerate recovery and improvepatient comfort. Acupressure, as a non-invasive treatment technique, has been known tohave the potential to relieve pain by stimulating certain points in the body. This studyaims to determine the effect of acupressure at the H7 and LI4 points on the intensity ofpost-cesarean section pain in mothers giving birth at the Bhayangkara Hospital TK1PUSDOKKES Polri in 2024. This study used a pre-experiment with a pretest-posttestwith a one-group pretest-posttest design. Sampling was carried out using a purposivesampling technique of 35 respondents. The analysis used a non-parametric test, theFriedman test. The Friedman test analysis showed a significant effect of acupressure atthe H7 and LI4 points on the intensity of post-cesarean section pain in mothers givingbirth with a p-value of 0.000. Acupressure at the H7 and LI4 points affects the intensityof post-cesarean section pain in mothers giving birth at the Bhayangkara Hospital Level1 Pusdokkes Polri in 2024. Mothers giving birth with post-cesarean section surgery areadvised to use the acupressure method to reduce dependence on analgesic drugs,thereby reducing the risk of side effects of drugs. They can be used as an alternative toconventional therapy in pain management.